Biosynthetic approaches to creating bioactive fungal metabolites: Pathway engineering and activation of secondary metabolism. Issue 24 (15th December 2016) - Motoyama, Takayuki; Osada, Hiroyuki
Graphical abstract: Abstract: The diversity of natural products is greater than that of combinatorial chemistry compounds and is similar to that of drugs. Compounds rich in sp 3 carbons, such as natural products, typically exhibit high structural complexity and high specificity to molecular targets. Microorganisms can synthesize such sp 3 carbon-rich compounds and can be used as excellent factories for making bioactive compounds. Here, we mainly focus on pathway engineering of two sp 3 carbon-rich bioactive indole alkaloids, fumitremorgin C and terpendole E. We also demonstrate the importance of activation of secondary metabolism by focusing on tenuazonic acid, a bioactive tetramic acid compound, as an example.